Academic Community Perception on the Quality of Nature-based Tourism Promotion Materials in Indonesia - Rini Untari; Ricky Avenzora; Dudung Darusman; Tutut Sunarminto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
The use of technology in the search and delivery of tourism information is growing, although, on the one hand, the conventional tourism information media in the form of printed materials and audio-visual is still a popular source of information for tourists. The decision to visit a tourist destination can be influenced by various factors, one of which is the influence of stimulus from promotional media. Problems that occur, the study of the role of promotion from a comprehensive and integrated perspective has not been done much. Many promotions are interpreted as an effort to convey information to the stage of carrying out purchasing/travel activities. The purpose of this article is to analyze the perceptions of the academic community regarding the meaning of promotion through printed and audio-visual material for nature-based tourism in a comprehensive and integrated manner, as well as to determine the factors that influence decision-making by the academic community to actually visit nature-based tourism destinations. The distribution of questionnaires was conducted using a sample of academic community consisting of three categories, namely, lecturers, ecotourism students, and communication students with a total of 270 respondents to assess printed and audio-visual material. Data analysis was performed using One Score One Indicator Scoring System, Kruskal Wallis Test, and Dunn test. The results of the study show that tourism promotion can be effective and needs to implement seven phases of comprehensive and integrated promotion meaning. The opinions of the respondents of the academic community are not polar and illustrated the factors that influence the decision to do an actual visit. Factors that influence the form of psychological factors (motivation, the intensity of exposure to information about natural tourism), besides personal factors and demographic characteristics of respondents. The implications of this study regarding the promotion of effective nature-based tourism need to pay attention to tourist segmentation from various perspectives, both psychological, personal, environment and demographic, especially the promotion of nature-based tourism, besides implementing promotion in the context of more comprehensive and integrated meaning to run more effectively. Keywords: material promotion, natural based tourism, perception, promotion